2006
DOI: 10.1080/11250000600917953
|View full text |Cite
|
Sign up to set email alerts
|

Hsp levels in toad heart are independent of temperature and pharmacological stimuli

Abstract: Expression of Hsp70 in heart and skeletal muscle in two species of toads (Bufo viridis and B. regularis) that reside in different climatic regions and differ profoundly in their temperature sensitivity was studied at room temperature and upon various acclimation conditions. The effects of hypoxia, phenylephrine and clonidine on heart rate, ECG and Hsp70 expression were also investigated. High and variable levels of Hsp70 were detected in heart tissue of both species, compared with Hsp70 levels detected in skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Due to the commercial antibody we used, cross-reacting with several HSP70 family members, the HSP70 levels we found may be a reflection of inducible, constitutive, or both forms of HSPs (HSP/HSC). Notwithstanding, in terms of the total amount of HSPs, intraspecies comparisons preserve their validity as suggested by other authors using the same type of antibody (Airaksinen et al, 2003;Chapovetsky and Katz, 2006).…”
Section: Protein Extraction Western Blotting and Quantification Of supporting
confidence: 67%
See 1 more Smart Citation
“…Due to the commercial antibody we used, cross-reacting with several HSP70 family members, the HSP70 levels we found may be a reflection of inducible, constitutive, or both forms of HSPs (HSP/HSC). Notwithstanding, in terms of the total amount of HSPs, intraspecies comparisons preserve their validity as suggested by other authors using the same type of antibody (Airaksinen et al, 2003;Chapovetsky and Katz, 2006).…”
Section: Protein Extraction Western Blotting and Quantification Of supporting
confidence: 67%
“…The strategy of expressing hsp genes continuously is adopted by other several organisms belonging to animals and protists living in very cold environments of polar and temperate zones to avoid protein denaturation due to low temperatures (Joplin et al, 1990;Yocum et al, 1991;Denlinger et al, 1992;Lee et al, 1995;Feder and Hofmann, 1999;Carpenter and Hofmann, 2000;La Terza et al, 2001;Place and Hofmann, 2005). According to Chapovetsky and Katz (2006), the presence of constitutively high levels of HSPs confers the capacity to respond promptly to any variation of environmental conditions. Zhang et al (2011) showed a consistent increase (1.5-to 2.0-fold) of HSP70 and other constitutive HSPs in the freeze-tolerant gall fly larvae of Eurosta solidaginis Fitch, 1855 (Diptera, Tephritidae) over late autumn-winter when they enter diapausa than in other periods of the year.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the commercial antibody we used, cross-reacting with several Hsp70 family members, the Hsp70 levels we found may be a reflection of inducible, constitutive or both forms of heat shock proteins (Hsp/Hsc). Notwithstanding, in terms of total amount of heat shock proteins, intra-and inter-species comparisons preserve their validity as suggested by other authors using the same type of antibody (Airaksinen et al 2003;Chapovetsky & Katz 2006).…”
Section: Discussionsupporting
confidence: 61%
“…Constitutive expression of Hsp70 may protect against expected accumulation of oxidative stress over prolonged aestivation and against the oxidative insult upon arousal, and presumably further helps C. alboguttata to 'absorb' temperature fluctuations during aestivation. Constitutive expression of HSPs are a strategy common to amphibians (Chapovetsky and Katz, 2006) regardless of varying physiological tolerance to environmental stressors, and may be a strategy common to animals that undergo dormancy (Carey et al, 1999;Storey and Storey, 2011). Other HSPs with well-defined roles in muscle morphology and function such as Hsp27 (Folkesson et al, 2008;Sharp et al, 2006) and Hsc70 (heat shock cognate 70) via interactions with thiols (Hoppe et al, 2004) are also likely to be involved.…”
Section: Hsp70mentioning
confidence: 99%